Innovations in English language arts teacher education - Pinnegar, Stefinee E.; Hallman, Heidi L., 1976- (Bingley, U.K. : Emerald Group Publishing Limited, 2017)
Changes in the discipline of english language arts teacher education have produced a much more expansive understanding of literacy and of what teachers of English language arts do.This volume addresses these changes by featuring innovationboth theoretical and appliedin the field itself. Changes in the field of English language arts teacher education suggest a need to also examine how teachers approach learning to teach in a field that has so quickly evolved. This book seeks to understand how a future teaching force will approach this changing landscape and how we, as English teacher educators, might effectively prepare them to do so.
Prelims -- Part I: Toward a broader vision of English teacher education -- Part II: Lenses for Preparing Prospective Teachers to Teach English Language Arts -- Part III: Social Justice Oriented English Language Arts Teacher Preparation.
Includes bibliographical references.
Keywords: Education, Distance, Open & Online Education; Educational equipment & technology, computer-aided learning (CAL).; Teachers -- Language -- Training of; Teachers -- Language -- Methodology